Pendampingan Guru Berbasis Photovoice untuk Mengatasi Burnout Akademik - Riswani Riswani; Zarkasih Zarkasih; Lailatul Munawwaroh (COMMUNITY SERVICE JOURNAL OF ECONOMICS EDUCATION, 2026)
Academic burnout is a serious issue among madrasah students because it affects motivation, emotional well-being, and learning engagement. Guidance and counseling teachers play an important role in helping students manage academic pressure, yet many still need practical and participatory methods to understand students’ emotional conditions. This community service program aimed to strengthen guidance and counseling teachers’ capacity to identify and address students’ academic burnout through photovoice. The program was conducted in a Madrasah Tsanawiyah in Pekanbaru. The participants were two guidance and counseling teachers and ten eighth-grade students with high academic burnout tendencies. The activity used a participatory approach through coordination, teacher training, student identification, photovoice implementation, reflective discussion, and evaluation. Data were collected through questionnaires, interviews, student reflections, photo analysis, observation, and final evaluation. The results showed that teachers improved their understanding of academic burnout and their skills in facilitating visual-based reflection. Students responded positively because photovoice helped them express academic pressure through photos and simple narratives. The program produced training materials, photovoice guidelines, visual documentation, and counseling strategies that can be continued by the madrasah.